Unmet legal and social advocacy needs of children with sickle cell disease: Implications for health care payer costs. (January 2018) - Sonik, Rajan A.; Teasdale, Sarah; Parish, Susan L.; Champigny, Maria; Sprinz, Philippa G.
Abstract: Previous studies of advocacy needs faced by children and families have not differentiated needs that require attorney involvement ("legal advocacy needs") from needs best addressed by social workers or lay advocates ("social advocacy needs"). Studies have also not examined the relationship between either type of need and health care costs. We developed a novel, replicable process to differentiate between legal advocacy needs and social advocacy needs. We then collected cross-sectional data from a sample of 52 children with sickle cell disease who were at least 1 year of age, a population with high advocacy needs and high health care costs. Mean annual health care costs to payers for children whose families had a least one legal advocacy need were 16, 314, compared to 5552 for children in families with no legal advocacy needs ( P = 0.007). After adjusting for covariates, the presence of a legal advocacy need was associated with 12, 040 more in health care costs to payers ( P = 0.02). Whether interventions to prevent and resolve legal advocacy needs can reduce health care costs by addressing the social determinants of health warrants future study. Highlights: We propose a novel process to distinguish between social and legal advocacy needs. We apply this process to children with sickle cell disease, a high need population. We associate identified needs with health care payer costs. We successfully identify distinct social and legal advocacy needs. Having an unmet legal advocacy need was associated with higher payer costs.